Zaangażowanie pracowników. Perspektywa koopetycji w organizacji = Work engagement. A perspective on coopetition in the organization - Moczulska, Marta
The book emphasizes employee engagement, highlighting its significance in the functioning of modern organizations. Taking a scientific approach to engagement (i.e. work engagement), considering the assumptions of concepts related to this issue, including predictors and sources, the main goal is to determine the possibilities of shaping work engagement through the combination of collaboration and competition, known as coopetition within the organization. It was realized by (1) analyzing each issue and (2) conducting research. The method of systematic literature review was used.
Keywords: zaangażowanie pracowników; koopetycja; współdziałanie; rywalizacja; organizacja; employee/work engagement; coopetition; collaboration; competition; organization